EFECTIVENESS OF USING A COMBINATION OF HYDROGEL AND HYDROCELLULAR FOAM IN THE PROCESS OF AUTOLYTIC DEBRIDEMENT IN HEALING DIABETIC ULCERS - Adnan Dhanny Diharja; Popi Sopiah; Rafika Rosyda (Buletin Veteriner Udayana, 2024)
Diabetic ulcers are a chronic complications of diabetes mellitus, which can increase the prevalence of morbidity and mortality in diabetes mellitus sufferers. To prevent this incident, diabetic ulcers, which are chronic wounds, need to be given proper and correct wound care. This research aims to determine the effectiveness of using a combination of hydrogel and hydrocellular foam in the autolytic debridement process for healing diabetic ulcers. This case report involves two respondents suffering from diabetes mellitus complicated by diabetic ulcers. This wound care intervention was carried out by a certified expert nurse eight times within a period of 14 days. Then, in assessing the progress of wound healing in the two respondents, the researcher used the Wocare for Indonesian Nurses (WINNERS) Scale observation sheet. The results of the study showed that the condition of the diabetic ulcers in both respondents experienced healing, which was characterized by increased growth of granulation tissue and epithelialization at the edges of the wound; the diameter and depth of the wound decreased; the GOA in the wound decreased; the characteristics of the exudate changed; and the amount of exudate decreased. The use of a combination of hydrogel and hydrocellular foam, which has proven to be effective in assisting the autolytic debridement process and increasing the speed of wound healing, can be carried out on various types and severity of wounds without causing any side effects.